(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To compare the efficacy of pain reduction during and after forearm and hand surgery in children using ultrasound-guided axillary brachial plexus block with Levobupivacaine 0.2% versus Levobupivacaine 0.25%. Subjects and methods: This study was conducted on 60 patients (aged 3-16 years) receiving axillary brachial plexus block at the Department of Anesthesiology and Intensive Care, National Children’s Hospital. Patients were randomly assigned to 2 groups: group 0.2 which used Levobupivacaine 0,2%, and group 0.25 which used Levobupivacaine 0,25%. Both groups used a volume of 0.5 ml/kg, maximum 20 ml. Results: The two groups were comparable regarding general characteristics: mean age 7.25 ± 3.34 years; weight 26.71 ± 10.39 kg; height 120.07 ± 17.93 cm; surgical duration 61.45 ± 22.19 minutes (p > 0.05). The efficacy of intraoperative anesthesia was good in both groups (100%). The duration of sensory and motor block for group 0.2 was 255.17 ± 43.10 minutes and 214.40 ± 38.46 minutes, respectively, and for group 0.25 was 356.97 ± 46.35 minutes and 311.53 ± 43.94 minutes (p < 0.001). The duration of analgesia for group 0.2 and group 0.25 was 367.87 ± 44.25 minutes and 414.30 ± 50.01 minutes, respectively (p < 0.05). The number of times additional analgesics were administered within 24 hours post-surgery was comparable between the two groups (p > 0.05). 2/60 cases reported pain at the injection site, 1/60 cases reported nausea. No excessive sedation or severe adverse effects were recorded. Conclusion: Both groups achieved good intraoperative anesthetic efficacy. Group 0.2 had an earlier recovery time for sensory and motor function (p < 0.001), and a shorter postoperative analgesia time (approximately 47 minutes less on average) compared to group 0.25 (p < 0.05). There was no difference in the number of times rescue analgesics were administered between the two groups over 24 hours after surgery (p > 0.05).